Influence of organic solvent mixtures on biological membranes. Issue 9 (September 1985) - Gustafson, C; Tagesson, C
Abstract : A simple experimental model was used to study the influence of organic solvents and solvent mixtures on the integrity of biological membranes. Radiolabelled membranes were prepared biosynthetically by growing Escherichia coli in the presence of 14C-oleic acid; the bulk of the radioactivity was incorporated into 14C-phosphatidylethanolamine, the predominant phospholipid species in E coli membranes. The radiolabelled bacteria were incubated at 37 degrees C in the presence of solvent, and the mixture filtrated through a Millipore 0.45 micron filter. This filtration retained radiolabel associated with the bacteria, and only radiolabel released as a result of solvent action was allowed through the filter. The radioactivity in the filtrate was then counted and expressed as a percentage of the total radioactivity. Results showed that aliphatic alcohols released membrane constituents in relation to their hydrocarbon chain length (1-propanol greater than 2-propanol greater than ethanol greater than methanol); the effects of aliphatic alcohols were potentiated by acetone, ethyl methyl ketone, ethylene glycol, and N, N'-dimethylformamide, and the effects of ethanol were potentiated by 1-butanol, benzyl alcohol, and ethylacetate. These findings point to the possibility that certain mixtures of organic solvents are more damaging to membranes than the components of the mixture would indicate, and suggest that the experimental model used might help in showing mixtures that are particularly harmful.